Polymorphisms CYP2R1 rs10766197 and CYP27B1 rs10877012 in Multiple Sclerosis: A Case-Control Study - A. Martinez-Hernandez; E. E. Perez-Guerrero; M. A. Macias-Islas; C. A. Nava-Valdivia; A. Villagomez-Vega; B. Contreras-Haro; Y. E. Garcia-Ortega; Y. Esparza-Guerrero; S. G. Gallardo-Moya; J. I. Gamez-Nava; L. Gonzalez-Lopez; E. Oliva-Flores; et al. (Journal of Immunology Research)
Background. Multiple sclerosis (MS) is a chronic autoimmune inflammatory disease. Low vitamin D levels have been reported to be a risk factor for MS, and genetic variances could be implicated. The aim of this study was to evaluate the association of MS with rs10766197 polymorphism of CYP2R1 gene and rs10877012 polymorphism of CYP27B1 gene. The second aim was to analyse whether these polymorphisms are associated with the severity of the progression of MS. Material and Methods. In a case-control study, we included 116 MS patients and 226 controls, all of whom were Mexican Mestizo. MS was diagnosed by McDonald criteria (2017). A complete neurological evaluation was performed to evaluate the severity of disease progression. Serum 25-hydroxyvitamin D [25(OH) vitamin D] levels were measured by ELISA. Single nucleotide polymorphisms rs10766197 of CYP2R1 gene and rs10877012 SNP of CYP27B1 gene were genotyped by real-time PCR. Results. Serum 25(OH) vitamin D levels were lower in MS patients than in controls (p=0.009). No differences were observed between serum 25(OH) vitamin D levels of MS patients with severe progression compared to low progression (p=0.88). A higher frequency of the A allele of CYP2R1 rs10766197 was observed between MS patients and controls (p=0.05). No differences were observed in the frequency of T allele of CYP27B1 rs10877012 (p=0.65). In subanalysis, patients with GA+AA genotypes of CYP2R1 rs10766197 had an increased risk of MS compared to controls (p=0.03). No increased risk was observed in GT+TT genotypes of CYP27B1 rs10877012 (p=0.63). No differences were observed in allele frequencies of either polymorphism between patients with severe vs. low disease progression. Conclusion. Lower serum 25(OH) vitamin D levels were observed in MS patients than in controls, although these levels were not associated with disease progression. Carriers of GA+AA genotypes of CYP2R1 rs10766197 had an increased risk of MS. None of these polymorphisms was associated with severe progression of MS.